Investigation Moisture Damage Resistance of Asphalt Mixture Containing Crumb Rubber - Mohd Haziq Fitri Hisham; Rosnawati Buhari (Recent Trends in Civil Engineering and Built Environment, 2024)
Moisture content in pavement or asphalt mixture was commonly can cause major defect at the road such as potholes that can be dangerous to the road users. The dry process and wet process were the two conventional ways of incorporating the crumb rubber into asphalt mixtures. Dry process got more advantages rather than wet process. This study aims to determine the Optimum Bitumen Content (OBC) and also the Indirect Tensile Strength (ITS) of rubberized asphalt mixture. 1%, 2% and 3% of crumb rubber mixes were added by weight of aggregate The test that involve were air void density, specific gravity, penetration, softening and volumetric test to determine the Optimum Bitumen Content (OBC). For the performance test, ITS were conducted which was dry and wet method to produce ITSr to analysis the resistance of moisture content. The expected result was showed that the less of CR powder was the higher resistance of moisture content in the mixture. The amount of OBC that were achieved was 5.5% by weight if aggregate. The result for ITS by adding 1%, 2% and 3% of CR were 1139.72kN, 846.06kN and 778.79kN for dry sample and 1068.07kN, 711.69kN and 575.2kN. The ITSr result was increasing from 86.11% to 98.71% and then decreasing to 84.12% and 73.87% for the percentage of crumb rubber 2% and 3%. The Amount of CR powder effect the moisture content resistance. The more the CR in the asphalt mixture, the less strength it can bear.